(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the issues of diagnosing learning. It also explains in detail the importance of assessment methods in improving educational effectiveness.